Pengaruh Transparansi dan Akuntabilitas Pengelolaan Dana Wakaf terhadap Minat Masyarakat Berwakaf Tunai di MBS Ki Bagus Hadikusumo - Akhmad Santoso; Abdurrahman Hakim; Dedi Junaedi; Muhammad Fathan Mujahid (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the influence of transparency and accountability in the management of waqf funds on the public's interest in cash waqf at MBS Ki Bagus Hadikusumo. The research employed a quantitative method with a survey approach, collecting data through questionnaires from 80 respondents. The analysis results show that transparency does not have a significant partial effect, while accountability has a significant effect on the interest in cash waqf. Simultaneously, transparency and accountability have a significant effect on public interest. This study highlights the importance of accountable waqf governance in increasing public participation. It is recommended that waqf institutions enhance transparency, accountability, and carry out continuous education efforts. Keywords: Transparency, Accountability, Cash Waqf, Public Interest.